Planning and managing a complex multisite study in the age of technology. Issue 4 (30th October 2019) - Miller, Carrie Westmoreland; Greenawalt, Julia A.; Kardong‐Edgren, Suzan (Suzie); Oermann, Marilyn H.; Molloy, Margie; Mudra, Vickie; Rogers, Nancy; Mondragon, Lissette; Cespedes, Anna; Frost, Erica; Causey, Regina; Webb, Suzanne; et al.
Abstract: A 2‐year long, multisite research study that evaluated cardiopulmonary resuscitation skill decay among nursing students was conducted at 10 schools of nursing across the United States. The study was conducted in two phases and required carefully timed sessions for skill performance. Multisite studies in nursing education need to be carefully planned. Time delays should be anticipated with processes and Institutional Review Board protocols across sites. All team members were trained and consistently supported during the entire study. While challenges and obstacles were identified, innovative solutions were implemented that assisted the research team to successfully complete the study. The use of new and existing technology allowed the team to surmount many of the challenges encountered in this study. The purpose of this article is to describe the logistics, processes, challenges, and lessons learned related to conducting a complex multisite study. Take‐away Key Points: 1. A shared mental model at the outset of the execution of the study promoted smooth day‐to‐day operations. 2. Utilizing applicable technology to enhance communication was valuable to successful execution of the objectives of the study. 3. Anticipate for staff turnover and participant retention issues. 4. Anticipate and plan for continuous and rigorous IRB compliance administrative workload. 5. A multisite study is not a starting point for a novice researcher. Begin with smaller pilot studies and then progress to more complex, multisite studies.